Two-photon fluorescence and MR bio-imaging of endogenous H2O2 in the tumor microenvironment using a dual-mode nanoprobe. Issue 51 (2nd June 2021) - Zhong, Hongmei; Yu, Shengrong; Li, Bingqian; He, Kangdi; Li, Dian; Wang, Xiao; Wu, Yong-Xiang
Abstract : The dual-mode bio-imaging nanoprobe, TP-CQDs@MnO2, has been developed for the TP fluorescence and MR imaging of endogenous H2 O2 in the TME; it achieved high selectivity, a great signal-to-noise ratio, a limit of detection of 1.425 pM for H2 O2, and a two-photon tissue penetration depth of 280 μm. Abstract : The dual-mode bio-imaging nanoprobe TP-CQDs@MnO2, based on two-photon carbon quantum dots and MnO2, has been developed for the two-photon fluorescence and MR imaging of endogenous H2 O2 in the tumor microenvironment, and it achieved high selectivity, a great signal-to-noise ratio, a limit of detection (LOD) of 1.425 pM for H2 O2, and a two-photon tissue penetration depth of 280 μm.